Modeling Confirmation Bias and Peer Pressure in Opinion Dynamics - Liu, Longzhao; Wang, Xin; Chen, Xuyang; Tang, Shaoting; Zheng, Zhiming (Frontiers in Physics, 2021)
Confirmation bias and peer pressure were regarded as main psychology origins of personal opinion adjustment. Each of them showed substantial impacts on the formation of collective decisions. Nevertheless, few attempts have been made to study how the interplay between these two mechanisms affects public opinion evolution on large-scale social networks. In this paper, we propose an agent-based model of opinion dynamics which incorporates the conjugate effect of confirmation bias (characterized by the population identity scope and initiative adaptation speed) and peer pressure (described by a susceptibility threshold and passive adaptation speed). Firstly, a counterintuitive non-monotonous phenomenon arises in the homogeneous population: the number of opinion clusters first increases and then decreases to one as population identity scope becomes larger. We then consider heterogeneous populations where `impressionable' individuals with large susceptibility to peer pressure and `confident' individuals with small susceptibility coexist. We find that even a small fraction of impressionable individuals could help eliminate public polarization when population identity scope is relatively large. In particular, the impact of impressionable agents would be greater if these agents are hubs. More intriguingly, while impressionable individuals have randomly distributed initial opinions, most of them would finally evolves to moderates. We highlight the emergence of these `impressionable moderates' who are easily influenced yet important in public opinion competition, which may inspire efficient strategies in winning competitive campaigns.